Commune, country and commonwealth : the people of Cirencester, 1117-1643 - Rollison, David, 1945- (Studies in early modern cultural, political and social history ;, 2011)
Commune, Country and Commonwealth' suggests that towns like Cirencester are a missing link connecting local and national history, in the immensely formative centuries from Magna Carta to the English Revolution. Focused on a town that made highly significant interventions in national constitutional development, it describes recurring struggles to achieve communal solidarity and independence in a society continuously and prescriptively divided by gross inequalities of class and status. The result is a social and political history of a great trans-generational epic in which local and national influences constantly interacted. From the generation of Magna Carta to the regicides of Edward II and Richard II, through the vernacular revolution of the 'long fifteenth century' and the chaos of state reformations to the great revival that ended in the constitutional wars of the 1640s, the epic was united by strategic location and by systemic, 'structural' inequalities that were sometimes mitigated but never resolved. Individual and group personalities emerge from every chapter, but the 'personality' that dominates them all, Rollison argues, is a commune with 'a mind of its own', continuously regenerated by enduring, strategic realities. An afterword describes the birth and development of a new, 'rural' myth and identity and suggests some archival pathways for the exploration of a legendary English town in the modern and postmodern, industrial and post-industrial epochs. DAVID ROLLISON is Honorary Research Associate in History, University of Sydney.